2008
DOI: 10.1038/ni.1638
|View full text |Cite
|
Sign up to set email alerts
|

Function of TRADD in tumor necrosis factor receptor 1 signaling and in TRIF-dependent inflammatory responses

Abstract: Tumor necrosis factor receptor 1 (TNFR1) and Toll-like receptors (TLRs) regulate immune and inflammatory responses. Here we show that the TNFR1-associated death domain protein (TRADD) is critical in TNFR1, TLR3 and TLR4 signaling. TRADD deficiency abrogated TNF-induced apoptosis, prevented recruitment of the ubiquitin ligase TRAF2 and ubiquitination of the adaptor RIP1 in the TNFR1 signaling complex, and considerably inhibited but did not completely abolish activation of the transcription factor NF-kappaB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
203
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(214 citation statements)
references
References 39 publications
7
203
0
4
Order By: Relevance
“…Indeed, in recent studies in which TRADD À/À MEFs failed to activate NF-kB in response to TNF, TRADD À/À bone marrow-derived macrophages (BMDM) did so to the same extent as WT BMDMs. 35,36 This implies that the signalling platform assembled on TNFR1 is more plastic than previously thought, and that the function of certain molecules in this complex is interchangeable.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, in recent studies in which TRADD À/À MEFs failed to activate NF-kB in response to TNF, TRADD À/À bone marrow-derived macrophages (BMDM) did so to the same extent as WT BMDMs. 35,36 This implies that the signalling platform assembled on TNFR1 is more plastic than previously thought, and that the function of certain molecules in this complex is interchangeable.…”
Section: Discussionmentioning
confidence: 66%
“…Along the same line, the enhancement of TLR3-triggered apoptosis when TRADD is depleted could be explained by the involvement of this adapter in the recruitment of TRAF2 to RIP1, as recently suggested for TNFRI. 30 Indeed, TRADD was shown to be required for RIP1 ubiquitination and for proper NF-kB and MAP kinase activation in response to TLR3 stimulation. 30 However, the N-Ter portion of TRIF can also bind TRAF2 directly, irrespective of TRADD.…”
Section: Discussionmentioning
confidence: 99%
“…30 Indeed, TRADD was shown to be required for RIP1 ubiquitination and for proper NF-kB and MAP kinase activation in response to TLR3 stimulation. 30 However, the N-Ter portion of TRIF can also bind TRAF2 directly, irrespective of TRADD. 31 Thus, as previously reported for TNFRI, 27 TRADD appears to protect cells from TLR3-triggered apoptosis through a positive regulatory function as regards RIP1 ubiquitination, although the exact mechanism of its action remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…TRADD was discovered in 1995 91 but definitive genetic evidence of the role of TRADD in TNFR1-mediated apoptosis was only recently reported. 92,93 TRADD deficiency blocked TNFR1-induced cell death induced by TNF þ CHX in vitro and by TNF þ GalN in vivo, thereby establishing the essential role of TRADD in proapoptotic signaling downstream of DRs. These studies also analyzed the components of Complex 1 recruited to TNFR1 and found that in the absence of TRADD, less RIP1 and no TRAF2 were associated, and that ubiquitination of RIP1 was markedly reduced.…”
Section: Dr Signaling Is Regulated By Ubiquitinationmentioning
confidence: 99%